The effects of hyperoxia, hypoxia, and ischemia/reperfusion on the activity of cytochrome oxidase from the rat retina - Sisková, A; Wilhelm, J (Physiological research, 2001)
Cytochrome oxidase activity from the retina can be enhanced or depressed by free radical-mediated reactions both in positive and negative aspect. The greatest effect was exerted by ischemia/reperfusion, which significantly increased the fluorescent products of lipid peroxidation (358 %, P < 0.01) and inhibited the enzyme activity (14%, P < 0.001). After hyperoxia the fluorescent products slightly increased (192%, P < 0.05) as well as the enzyme activity (133 %, P < 0.05). Hypoxia had no effect on any of these parameters. Specific changes in the composition of fluorophores after ischemia/reperfusion were revealed in the fluorescence spectra. The fact that increased lipid peroxidation after hyperoxia and after ischemia/reperfusion does not produce the same effect upon cytochrome oxidase activity might be explained by changes in the kinetic behavior of cytochrome oxidase. In the control enzyme preparation, two binding sites for cytochrome c were observed. One was of the low-affinity (Km = 60 microM) and the other of the high-affinity (Km = 1.12 microM). After in vitro-initiated lipid peroxidation, the low-affinity binding site was lost and the activity measured under "optimum" conditions at a single cytochrome concentration was higher than in the controls. This implies that oxidative damage to cytochrome oxidase in vivo can be site-specific and its extent should be estimated by performing detailed kinetic analysis as otherwise the results might be misleading.
Keywords: Animals; Rats; reperfuzní poškození; Hypoxia; Kinetics; Electron Transport Complex IV; Rats, Wistar; Retina; hyperoxie; respirační komplex IV; Buffers; fluorescenční spektrometrie; peroxidace lipidů; hypoxie; Phosphates; Lipid Peroxidation; Male; Oxygen; Reperfusion Injury; okluze retinální arterie; krysa rodu Rattus; Retinal Artery Occlusion; retina; zvířata; mužské pohlaví; pufry; Spectrometry, Fluorescence; fosfáty; kinetika; kyslík; Hyperoxia; potkani Wistar